2002
DOI: 10.1161/01.cir.0000025631.68522.9d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Determinants of Ventricular Sympathetic Reinnervation After Orthotopic Heart Transplantation

Abstract: Background-It has been demonstrated that ventricular sympathetic reinnervation after cardiac transplantation improves exercise performance. The extent of reinnervation increases with time but is variable. Little is known about other influencing factors. Methods and Results-Seventy-seven nonrejecting transplant recipients were cross-sectionally studied by PET with the catecholamine analogue C-11 hydroxyephedrine at 4.8Ϯ3.5 years after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 25 publications
4
34
0
2
Order By: Relevance
“…Reinnervation of the heart after chronic ischemia (Vracko et al, 1990; Zhou et al, 2004; Hasan et al, 2006; El-Helou et al, 2008) or cardiac transplantation (Bengel et al, 1999; Estorch et al, 1999; Bengel et al, 2001; Bengel et al, 2002) fit this model of robust sympathetic regeneration. However, we found that a common injury affecting over a million people each year in the US (Roger et al, 2012) – cardiac ischemia-reperfusion – generates a scar that is refractory to reinnervation.…”
Section: Discussionmentioning
confidence: 93%
“…Reinnervation of the heart after chronic ischemia (Vracko et al, 1990; Zhou et al, 2004; Hasan et al, 2006; El-Helou et al, 2008) or cardiac transplantation (Bengel et al, 1999; Estorch et al, 1999; Bengel et al, 2001; Bengel et al, 2002) fit this model of robust sympathetic regeneration. However, we found that a common injury affecting over a million people each year in the US (Roger et al, 2012) – cardiac ischemia-reperfusion – generates a scar that is refractory to reinnervation.…”
Section: Discussionmentioning
confidence: 93%
“…Neither study established a relationship between time since HTX and response to atropine, in contrast to what is seen during sympathetic reinnervation. 12 This study demonstrated a significant difference in resting HR between those who responded to dobutamine and those who required additional use of atropine (Table II). A possible explanation for this could be the presence of differential reinnervation among these patients.…”
Section: Autonomic Reinnervationmentioning
confidence: 67%
“…Reinnervation may be time-dependent 11 or may be affected by such factors as age of donor and recipient, surgical complication rate, rejection, 12 and surgical technique. 13 Without a consensus regarding parasympathetic reinnervation of the heart in HTX patients, the usefulness of atropine as a chronotropic agent is questionable.…”
mentioning
confidence: 99%
“…However, the heart does not become fully reinnervated over time and some patients remain denervated late after surgery (15 years). Follow-up studies indicated that although time is a determinant of reinnervation, the likelihood of innervation is also dependent on donor and recipient age, duration and complexity of surgery [56], and diabetic status [57]. Perhaps most importantly, [ 11 C]-HED has been used to assess the significance of SNS innervation on cardiac function.…”
Section: Evaluation Of Innervation After Cardiac Transplantationmentioning
confidence: 99%